Group Learning in Optimizing the 5 Part of Collaborative Learning and Learning Performance - Imtiyaza, Muhammad Iffat; Said, Ibrahim Bin (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2022)
The method was obtained from the results of research in the form of classroom action research that uses 2 periods in class X-B MAN 3 Kediri and the topic of discussion is plants (plantae). By using a group learning style helps in the improvement process: 1) the teacher provides learning topics in cycle I to cycle II where the teacher finds it difficult to manage the class situation because students are still unfamiliar with the group learning model but in cycle II the teacher is able to manage the class because students already familiar with the group model; 2) the 5 parts of the collaborative learning style obtained results in the second cycle, level K amounted to 1.248%, level C amounted to 11.248%, and level B amounted to 87.5%; and 3) student learning performance which was calculated with an average score collateral average and profit at the end of the study from the beginning of the data, cycle I, and cycle II. The mean values ​​(54.7, 67.5, and 81.4) were the scores obtained and the end of the collateral learning resulted in the percentage (12.9%, 53.12%, and 93.75%). The research conducted at the end of the second cycle there were several students who scored (< 70) so that these students must be guided in understanding the material that has not been understood. The teacher must give thorough attention to all students in order to improve the 5 parts collaborative and student performance.